Immunomodulation by Processed Animal Feed: The Role of Maillard Reaction Products and Advanced Glycation End-Products (AGEs) - Teodorowicz, Malgorzata; Hendriks, Wouter H.; Wichers, Harry J.; Savelkoul, Huub F. J. (Frontiers in Immunology, 2018)
The immune system provides host protection to infection with pathogenic organisms, while at the same time providing tolerance upon exposure to harmless antigens. Thus, an impaired immune function is associated with increased susceptibility to infections with increased disease severity and thereby necessitating the therapeutic use of antibiotics. Livestock performance and feed efficiency, in addition to their health status, are dependent on the microbial load of their gut, the barrier function of the intestinal epithelium and the activity of the mucosal immune system, all of which can be modulated by dietary components. The majority of feeds that are consumed in pets and livestock have been processed. Processing promotes a non-enzymatic reaction between proteins and sugars called Maillard reaction (MR). Maillard reaction products (MRPs) and advanced Maillard reaction products (AGEs) determine taste, smell, and color of many food products therefore the MR is highly relevant for the feed industry. MRPs interact with different types of immune receptors, including the receptor for advanced glycation end products (RAGE) and immunomodulatory potential of feed proteins can be modified by Maillard reaction. This MR has become an important concern since MRPs/AGEs have been shown to contribute to increasing prevalence of diet-related chronic inflammatory states in the gut with negative health consequences and performance. The immunomodulatory effects of dietary MRPs and AGEs in livestock and pet animals are far less well-described, but widely considered to be similar to the relevant concepts and mechanisms obtained in the human field. This review will highlight immunological mechanisms underlying initiation of the innate and adaptive immune responses by MRPs/AGEs present in animal feeds, which are currently not completely understood. Bridging this knowledge gap, and taking advantage of progress in the human field, will significantly improve nutritional quality of feed and increase the prevention of diet-mediated inflammation in animals.